Pengembangan Variasi Mengajar - Sumiani HSB; Jefryanti Syafitri; Gusmaneli Gusmaneli (Universitas 45 Surabaya, 2024)
Developing teaching variations is an important effort to increase the effectiveness of the learning process in the classroom. In teaching, teaching variety includes the use of various techniques, methods and approaches that are adapted to the needs and learning styles of students. This research aims to analyze the effect of teaching variations on student motivation and learning outcomes. Using appropriate teaching variations can help maintain students' interest and involvement in learning, thereby having a positive impact on their academic achievement. The research results show that teaching variations involving collaborative activities, simulations, the use of technological media, and the application of active learning strategies have a significant impact in increasing student motivation and learning outcomes. Therefore, teachers are advised to continue to develop and integrate teaching variations in learning activities to create a more effective and enjoyable learning experience for students.